Absolute music in retrospective of intellectual history - Andriі Karpenko; Olena Karpenko (Cхід, 2017)
The history of the phrase absolute music has been studied by many theorists of music and music historians, while historians of philosophy proved to be rather reluctant to such syncretic concept. However, absolute music is exactly the case of non-philosophical appropriation of a philosophical category, which fits theoretical framework of the studies in intellectual history. Initial exploration on the synthesis of history of philosophy and musicology and music history has shown that the conceptual field of intellectual history enables the transition from abstract ideas to concrete social history of thought. It is proved that "absolute music" is not an authentic concept of music culture of the nineteenth century, but rather a good invention of new musical hermeneutics, which defined a period in the development of music and paradigm of concepts that characterized autonomy of musical form. The subject of historical and philosophical studies of the phrase "absolute music" lies in transformation of a philosophical term into a unit of aesthetic discourse, and later its reincarnation in the concept of musical historiosophy. Both philosophical and musicological approaches to the history of absolute music are based on the assumption that only theoretically relevant assertions and judgments appeal to the hermeneutic reconstruction and generalization, whereas political and social references of the discourse of absolute music can be left aside. So futher research shall focus on possibilities of how to reach the concrete social background of that form of thinking which employs the idiom absolute music.